The effects of leadership attributes and motivation to lead on preferred job characteristics: case study of undergraduates in Malaysian universities - Abdul Hamid, Jamaliah; D'Silva, Jeffrey Lawrence (Canadian Center of Science and Education, 2014)
The objective of this study was to examine the relationship between the leadership attributes and motivation to lead (MTL) of undergraduates in Malaysia with their inclination to choose specific types of job characteristics or job attributes. Many researches has proven that personality is positively related to preferred job characteristics, but no research to the researchers’ knowledge has been done on leadership attributes and motivation to lead with selected job characteristics. Data were collected from 711 undergraduates from Malaysian public universities. The results showed that leader attributes contributes a stronger predictive effect than the motivation or keenness to lead in determining the selection of specific job characteristics. This finding supports the research hypothesis that undergraduates who have been exposed to leadership training and development have gained greater emotional and cognitive maturity that enable them to be more open to a broader range of job characteristic types. No significant difference was observed between males and females, nor between Science and Humanity programs of study in the students’ selection of specific job characteristics. Findings, implications and directionsfor research are discussed.